Mrs Groff's mischievous book of motherhood management - Groff, Maggie ([North Sydney, New South Wales] : Penguin Random House Australia, 2019)
Warm, funny and wise, Mrs Groff's Mischievous Book of Motherhood Management is an irresistible voice for our time, championing common sense and skewering nonsense at every turn. Packed with a treasure trove of fascinating information about the female parent commonly known as 'mother' - and a multitude of hints, facts, cheats, ideas and curiosities - this little gift book will surprise and delight.
Includes bibliographical references.
Keywords: Motherhood -- Anecdotes; Motherhood -- Handbooks, manuals, etc; Motherhood -- Humor; Motherhood -- Miscellanea; Mothers -- Anecdotes; Families -- Anecdotes; Family & Health; Self-help & personal development; Australian